PENGGUNAAN KITOSAN DARI LIMBAH KULIT UDANG SEBAGAI INHIBITOR KEASAMAN TUAK - Fikriatun Nurhikmawati; Manuntun Manurung; A. A. I. A. Mayun Laksmiwati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
The research has been conducted to determine the ability of chitosan from shrimp shell as an inhibitor of tuak acidity. Isolation of chitin is done through three stages, namely deproteination, demineralization, and depigmentation. The deacetylation process of chitin into chitosan was accomplished with 50% (w/v) NaOH with a ratio of 1:10 at 90oC for 120 minutes. 15.33 g chitin was gained (15.33%), and 9.94 g chitosan or 9.94% were obtained with a degree of deacetylation of 69.87%. The optimum concentration of kitosan to inhibit tuak pH changes was 2% (w/v) thus providing a longer shelf life with lowest acidity (pH).